Estrategias didácticas para la conservación de la biodiversidad a partir de la utilización de biohuertos. - Oliva, Antia T. (2022)
Research is transmitted whose objective was to propose a didactic strategy for the conservation of biodiversity from the use of bio-sites. Students of the tenth year of higher basic education of the school of basic education “Antonio Elizalde" participated. The loss of biodiversity is one of the great problems facing humanity. In this sense, the disappearance of species is an environmental problem that is becoming more important every day. In the present work the qualitative approach was used. This type of research considers the perspectives on the phenomena from the participants themselves, has a flexible design and assumes to a large extent an inductive character Within this methodology the ethnographic research design was implemented. The central category was to analyze was the conservation of biodiversity by students. From the analysis of the data one of the aspects to highlight in this ethnographic research was the prevailing answer about the lack of care and conservation of the biodiversity of their environment, do not know how to manage their natural resources in a framework of respect for the natural reality, an aspect reflected in negative activities on the care of the biodiversity that surrounds them.